Problematika Pelaksanaan Haji: Studi Atas Polemik Seputar Mina Jadid dan Perluasan Tempat Sa’i - Harahap, Gultom; Khoirul Fata, Ahmad (Sekolah Tinggi Agama Islam Nurul Iman Bogor, 2022)
This article studies the problem that raises in the Hajj implementation, these are on Mina Jadid (the new Mina) and on the fleshed out of the Sa’i place. This article is wrotte for a reason that the problems make polemics in the public sphare. This article brings the polemics forward to show the public, and all their argumentation. After that, the authors take a conclusion based on better argument. From the study, authors can take a conclusion that the fleshed out of the Mina and Sa’i place are requirement in this time, and never make a changed ritual of hajj.